2013
DOI: 10.1007/s11334-013-0200-4
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of formalising design guidelines: a case study on the predictability of drug infusion pumps

Abstract: A demonstration is presented of how automated reasoning tools can be used to check the predictability of a user interface. Predictability concerns the ability of a user to determine the outcomes of their actions reliably. It is especially important in situations such as a hospital ward where medical devices are assumed to be reliable devices by their expert users (clinicians) who are frequently interrupted and need to quickly and accurately continue a task. There are several forms of predictability. A definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…The typed higher-order logic of the Prototype Verification System (PVS) [8] has been used for the formal specification of many kinds of systems, including medical devices [3,7,6]. In the PVS, a system is modeled by a theory, i.e., a set of statements in the PVS logic language describing the system by means of variable, constant, and function definitions, and of axioms and theorems about them.…”
Section: Formalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The typed higher-order logic of the Prototype Verification System (PVS) [8] has been used for the formal specification of many kinds of systems, including medical devices [3,7,6]. In the PVS, a system is modeled by a theory, i.e., a set of statements in the PVS logic language describing the system by means of variable, constant, and function definitions, and of axioms and theorems about them.…”
Section: Formalizationmentioning
confidence: 99%
“…The latter have many causes, including ill-designed interfaces [6] and incorrect information about the patient. The issue with interfaces is aggravated by the fact that devices with the same purpose may have different interfaces, depending on vendor or model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rushby [24] used model checkers Murφ and SAL to verify mode confusion in a cockpit; Rukšėnas et al [21] used SAL to identify post-completion errors in infusion pumps; Campos and Harrison used IVY/NuSMV to analyze infusion pumps against properties such as consistency, visibility, and feedback [4,11]; and in our own work, we used SAL and Event-B/Rodin to analyze the data entry system of infusion pumps for their predictability [15,16] and other safety properties identified by FDA [22].…”
Section: Related Workmentioning
confidence: 99%
“…The present work builds on our previous research on the verification of medical device user interfaces [11,[14][15][16]22] and on user interface prototyping [19]. These previous efforts have demonstrated that formal methods can be used to identify human factors issues in reverse-engineered models of medical devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, hardly any concrete examples of model-based development of user interfaces have been explored that take account of human factors or human factors engineering. In our previous work, we illustrated how verification tools could be used to verify the design of commercial infusion pump user interfaces against properties that capture human factors concerns [4,6,13,14] and safety requirements [12]: potential issues were identified precisely, and verified design solutions that could fix the identified issues were presented. This work builds on our previous work, and extends it by introducing a model-based development approach for rapid prototyping of medical device user interfaces that are verified against given safety requirements.…”
Section: Introductionmentioning
confidence: 99%